Instrumentos eletrônicos de pagamento: seu uso e suas implicações na política monetária - Eder Fabricio Santos Souza (2010)
This dissertation proposes two discussions on the use of electronic instruments of payment: econometric analysis on the use of credit cards and debit cards in Brazil and a theoretical discussion about the effects of the use of these instruments on monetary policy. The econometric analysis consists of two models, an explanatory panel and a predictive VAR, which aim to estimate the relationship between acquirers and merchants on credit cards and debit cards markets. The results show the importance of exchange rate on the credit cards market. The theoretical discussion focuses on the implications of the increasing adoption of such instruments of payment on the effectiveness of monetary policy, based on an analysis of its transmission channels. The findings, in this case, vary depending on assumptions about the transmission mechanism of monetary policy and money endogeneity.